Research for Planning 1953-55 August 1955 - Planning Commission (Planning Commission Government of India, 1955)
The Research Programmes by the Planning Commission (1953-55) emphasize the strategic role of empirical research in guiding India’s socio-economic development under the First Five Year Plan. With an allocation of Rs. 50 lakhs, the Research Programmes Committee was established in July 1953, comprising leading economists and social scientists collaborating with universities and research institutions. The committee approved 59 research schemes across key areas: land reforms and farm management, savings, investment and employment, city surveys analyzing rural-urban migration, and social welfare initiatives for marginalized communities. These projects not only provided critical data for informed policy-making but also facilitated the training of over 750 research personnel, building a skilled workforce in socio-economic research. Additionally, coordination with foreign-sponsored research expanded collaborative opportunities, enhancing methodological rigor. Overall, the program underscored the importance of systematic, data-driven research in addressing development challenges, fostering academic engagement, and shaping policies aimed at national progress and equitable growth.
Research Programmes Committee Planning Commission
Keywords: Research Programmes; Planning Commission; Socio-Economic Research; Land Reforms; Farm Management; Urbanization Studies; Savings and Investment; Employment Studies; Social Welfare; University Collaboration; Research Training; Policy Development